Yobel: Periode, Sosial, Ekonomi, dan Teologi - Laoly, Nepho Gerson (STT Injili Indonesia Medan, 2021)
The literature on Jubilees discussesÂ implications of acquiring the Land of Canaan (Palestine). Jubilee had a high degree of law in aspects of The Life of the Israelites, especially the administrating of the territory of the land of Canaan.Â However, there are also scholars who think of jubilees as a rule instituted by priests in the period of exile or in the period of return from exile. Jubilee writing is in the background of the Ancient Near East, the Second Temple, and the writing of the gospels that use jubilee years such as Luke.Â In addition, jubilees are the basic arguments for liberating and socialist theology or related to contemporary agendas that use the word